Solvents, Ionic Liquids and Solvent Effects - Glossman-Mitnik, Daniel; Maciejewska, Magdalena (IntechOpen, 2020)
Solvents and ionic liquids are ubiquitous within our whole life since ancient times and their effects are actually being studied through basic sciences like Chemistry, Physics and Biology as well as being researched by a large number of scientific disciplines.This book represents an attempt to present examples on the utility of old and new solvents and the effects they exercise on several fields of academic and industrial interest. The first section, Solvents, presents information on bio-solvents and their synthesis, industrial production and applications, about per and trichloroethylene air monitoring in dry cleaners in the city of Sfax (Tunsia) and on the synthesis of polyimides using molten benzoic acid as the solvent. The second section, Ionic Liquids, shows information about the synthesis, physicochemical characterization and exploration of antimicrobial activities of imidazolium ionic liquid-supported Schiff base and its transition metal complexes, the technology of heterogenization of transition metal catalysts towards the synthetic applications in an ionic liquid matrix, the progress in ionic liquids as reaction media, monomers, and additives in high-performance polymers, a pre-screening of ionic liquids as gas hydrate inhibitor via application of COSMO-RS for methane hydrate, the extraction of aromatic compounds from their mixtures with alkanes from ternary to quaternary (or higher) systems and a review on ionic liquids as environmental benign solvent for cellulose chemistry. The final section, Solvent Effects, displays interesting information on solvent effects on dye sensitizers derived from anthocyanidins for applications in photocatalysis, about the solvent effect on a model of SNAr reaction in conventional and non-conventional solvents, and on solvent effects in supramolecular systems.